THE EFFECT OF SINTERING METHODS ON THE MECHANICALPROPERTIES OF MGO-PSZ/YSZ DENTAL CROWN - Grace Pasaribu, Gisella
Nearly 57.6% of the Indonesian population experiences dental and oral health issues caused by tooth decay or infections that can lead to more serious health problems. One of the treatment efforts involves the installation of zirconia-based dental crowns. However, mechanical properties such as fracture toughness need improvement to prevent margin chippings, and one commonly used material for enhancement is MgO, known to improve the mechanical properties of dental crowns. In this study, MgO-PSZ/YSZ synthesis was conducted using wet ball milling and sintering. Varied parameters included sintering methods, namely single-step sintering and two-step sintering, and sintering temperatures at 1500°C, 1300°C, and 1300 C? decreased to 1150 C? . Additionally, PEG-6000 and TiO2 were added. The two-step sintering method resulted in a denser and more uniform morphology compared to the single-step sintering method. Using the two-step sintering method at a temperature of 1300°C successfully increased its fracture toughness value to 19.48 MPa.m1/2, as well as a density of 3.37 g/cm3, and a hardness value of 9.1 GPa. However, the two-step sintering method has not yet demonstrated superior mechanical properties compared to the single-step sintering method at a temperature of 1500 ?C.